Transcriptomic resources for evolutionary studies in flat periwinkles and related species - Marques, João P. (Sci Data, 2020)
The flat periwinkles, Littorina fabalis and L. obtusata, comprise two sister gastropod species that have an enormous potential to elucidate the mechanisms involved in ecological speciation in the marine realm. However, the molecular resources currently available for these species are still scarce. In order to circumvent this limitation, we used RNA-seq data to characterize the transcriptome of four individuals from each species sampled in different locations across the Iberian Peninsula. Four de novo transcriptome assemblies were generated, as well as a pseudo-reference using the L. saxatilis reference transcriptome as backbone. After transcripts’ annotation, variant calling resulted in the identification of 19,072 to 45,340 putatively species-diagnostic SNPs. The discriminatory power of a subset of these SNPs was validated by implementing an independent genotyping assay to characterize reference populations, resulting in an accurate classification of individuals into each species and in the identification of hybrids between the two. These data comprise valuable genomic resources for a wide range of evolutionary and conservation studies in flat periwinkles and related taxa.